Prognostic value of serial six-minute walk tests using tele-accelerometry in patients with chronic heart failure: A pre-specified sub-study of the TIM-HF-Trial. (29th August 2020) - Prescher, Sandra; Schoebel, Christoph; Koehler, Kerstin; Deckwart, Oliver; Wellge, Brunhilde; Honold, Marcus; Hartmann, Oliver; Winkler, Sebastian; Koehler, Friedrich
Abstract: Background: The six-minute walk test (6MWT) is an established functional test assessing exercise capacity and is used to predict clinical prognosis in patients with chronic heart failure (HF). Tele-accelerometry is a novel approach to activity monitoring using telemedical data transfer and allows a Tele-6MWT to be performed in an outpatient setting. It offers patients the option of performing simple serial follow-up tests in their own home. Aims: The aim of this study was to investigate the prognostic value of serial Tele-6MWTs using tele-accelerometry in patients with HF. Design/methods: In this proof-of-concept study, 155 patients with HF completed the Tele-6MWT in an outdoor setting once per month over a period of 0.25–21 months. We analysed the differences in the number of steps over time to predict hospitalization as a result of HF or death. Results: Patients with at least one event ( n = 31) recorded a lower number of steps and a shorter distance in Tele-6MWT at baseline compared with patients who remained event-free ( n = 124) (540.1 ± 78.4 steps vs. 601.8 ± 76.7 steps, P < 0.001 respectively; 353.2 ± 82.4 m vs. 418.8 ± 95.6 m, P < 0.001). Patients ( n = 19) who performed more than one Tele-6MWT prior to a clinical event showed no significant difference in the number of steps, regardless of whether the baseline test was compared with the last Tele-6MWT before the event or with the last two tests before the event. Conclusion: Tele-6MWT has a high predictive value with respect to hospitalization as a result of HF or death from any cause and the results were comparable with the prognostic impact of a conventional 6MWT. Therefore Tele-6MWT may be used as alternative test method in the home environment. However, there is no added prognostic value of repeating Tele-6MWTs on a monthly basis.